Rapid Plasma Reagin Card Test: A Screening Method for Syphilis in Antenatal Patients of Bastar, Chhattisgarh, India - Sahina Hassan; Satyaram Satapathy; Ratna Agrawal (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Sexually Transmitted Disease (STD) like syphilis is one of the important factor leading to adverse pregnancy outcomes in antenatal mothers. The infant and neonatal mortality rate itself is higher in the tribal region of Chhattisgarh like Bastar due to poor educational status and limited availability of health infrastructures. To prevent the disease related adverse pregnancy outcomes, early diagnosis and treatment of STDs is important by rapid screening method like Rapid Plasma Reagin (RPR) card test, which is comparatively cost effective tool available at clinical settings. Aim: To detect the incidence of syphilis among antenatal mothers of Bastar, Chattisgarh, India by using RPR card test. Materials and Methods: The present cross-sectional study was conducted on 150 blood samples of patients attending Obstetrics and Gynaecology, Outpatient and Inpatient Department (OPD and IPD) from August to October 2021. The samples referred to microbiology laboratory of Late Baliram Kashyap Memorial Government Medical College Jagdalpur, Chhattisgarh, India, were tested by RPR card test taking all aseptic precautions. The data were collected in Microsoft Excel sheet and results were presented in counts and percentages using descriptive statistics. Results: Out of 150 samples, 11 (7.33%) were tested positive by RPR card test while rest 139 (92.67%) were found negative. Out of the 11 (7.33%) samples which tested positive, 3 (27.27%) were from Antiretroviral Therapy (ART) centre (concurrent Human Immunodeficiency Virus (HIV) and syphilis positive), 7 (63.64%) were from Obstetrics and Gynaecology OPD and 1 (9.09%) sample was from labour ward. Age of the patients attending antenatal clinic ranged between 11-50 years with maximum patients 103 (68.67%) were in 21-30 years of age group. Conclusion: The RPR card test is one of the important cost effective, rapid screening tools for STDs like syphilis, especially in the resource poor areas like tribal region of Bastar, Chattisgarh, India. Comparatively higher percentage of syphilitic infection reported in the study may contribute in improving health infrastructure policies in the affected regions of Bastar, Chattisgarh, India.